2021
DOI: 10.1177/1744987120980154
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ caring behaviour and its correlation with moral sensitivity

Abstract: Background Different and contradictory results have been reported for nurses’ caring behaviour and moral sensitivity. Aims The present study aimed to examine the correlation between nurses’ caring behaviour and moral sensitivity. Methods The research was a descriptive, correlational study. Data were collected using moral sensitivity (range: 0–100) and caring behaviour (range: 24–144) questionnaires. A total of 250 nurses who worked in the clinical wards of Yasuj teaching hospitals in 2018, were selected by sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…This supports the previous findings that person‐centred care increases with increased age, career length (Sagong & Lee, 2016), and moral sensitivity (Park & Park, 2018). These findings are in line with the past findings that have shown a significant positive correlation between nurses' moral sensitivity and care behaviours (Afrasiabifar et al, 2021). Ertuğ et al (2014) revealed that moral sensitivity is associated with professional competence and high‐quality care, suggesting that nurses with high moral sensitivity can provide high‐quality patient care (Afrasiabifar et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This supports the previous findings that person‐centred care increases with increased age, career length (Sagong & Lee, 2016), and moral sensitivity (Park & Park, 2018). These findings are in line with the past findings that have shown a significant positive correlation between nurses' moral sensitivity and care behaviours (Afrasiabifar et al, 2021). Ertuğ et al (2014) revealed that moral sensitivity is associated with professional competence and high‐quality care, suggesting that nurses with high moral sensitivity can provide high‐quality patient care (Afrasiabifar et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The multiple regression analysis revealed that moral sensitivity was the most potent predictor of person-centred care. This result supports previous research (Afrasiabifar et al, 2021) that reported a significant correlation between nurses' moral sensitivity and care behaviour, and that nurses with high moral sensitivity could provide high-quality care to patients. Zhang et al ( 2020) performed a latent profile analysis according to nurses' moral sensitivity and identified the associations between the profiles and service behaviours.…”
Section: Predictors Of Person-centred Caresupporting
confidence: 91%
“…The first factor at the level of individual MHNs affecting PCC was moral sensitivity, which was high in this study. In parallel to this finding, the studies conducted by Afrasiabifar et al 14 and Mert Boga et al 35 also found a positive correlation between the moral sensitivity of nurses and caring behavior. This study identified that moral sensitivity affects both the perception and provision of MHNs' PCC.…”
Section: Discussionmentioning
confidence: 61%
“…Moral sensitivity is a significant attribute for nurses to identify and resolve ethical difficulties inherent in caring. 14 It is defined as an understanding of patients’ vulnerable situations and awareness of the moral meaning of decisions made in place of the patient. 12 Therefore, moral sensitivity would be an important factor to perform PCC.…”
Section: Introductionmentioning
confidence: 99%
“…Moral sensitivity is understood as an intuitive recognition of the conditions that can expose the patient to vulnerabilities that can be circumvented with an expanded view of the ethical and moral consequences of decision-making processes. 23,25,26 Professionals who have improved moral sensitivity can better manage ethical dilemmas than those who do not by broadening caring possibilities and clarifying the pathways for ethical decisionmaking in situations where autonomy is undermined with contradictions and restrictions of choices in light of the prognosis. [27][28][29] Therefore, we can infer that the limitations of nursing professionals in identifying ethical and moral conflicts can be overcome by strengthening their moral sensitivity.…”
Section: Discussionmentioning
confidence: 99%